Electroreduction of carbon dioxide (CO2) with flow cell system using tin-modified copper foam electrode - Syauqi, Muhammad Iqbal; Cahyani, Annisa Titi; Putri, Yulia Mariana Tesa Ayudia; Jiwanti, Prastika Krisma (Environmental and Materials, 2023)
In this study, modification of the copper foam (Cuf) electrode with tin (Sn) was carried out with the electrodeposition method for application in CO2 electroreduction.  Characterization using SEM EDX, FTIR, and XRD confirmed the presence of Cu2O, CuO, and SnO2 thin layer mixture on the Cuf/Sn electrode. The electrochemical characteristics of the electrode were examined by using the cyclic voltammetry (CV) technique. Under optimized conditions, electrochemical reduction of CO2 in a flow cell system. At the optimum condition of CO2 reduction in a flow cell system (flow rate of 75 mL/min and –0.6 V vs Ag/AgCl applied potential), the Cuf/Sn electrode exhibited a remarkable 75.79% with an 8.84 µmol/h formic acid production rate. In a comparable experiment, the Cuf/Sn flow system revealed a twofold improvement in the faradaic efficiency compared to the batch system and a threefold increase compared to the unmodified Cuf electrode in the flow system. Stability tests demonstrated consistent performance up to the 4th cycle, followed by a decline in the 5th cycle, potentially indicative of surface deterioration. The elevated performance is attributed to the synergistic effect of the Cu-Sn oxide layer, reinforcing the catalyst’s potential for efficient electrochemical CO2 reduction to formic acid.